Habilidade de permanência no rebanho (Stayability) de caprinos Saanen em condições tropicais, sob abordagem de análise de sobrevivência - Talita Andrade Ferreira (2019)
The objective of this study was to study the effect of morphometric, type and milk production on stayability and to estimate the genetic values and trends of Saanen goats in tropical environments in different Brazilian herds. For this, a Cox regression model and the Kaplan-Meier estimator were used for the mo- teretric and type traits. The effect of the productive traits on the (stayability) were analyzed using the Weibull risk animal model, on the relative risk of discarding goats. To estimate the components of variance and covariance, the linear-threshold model was used by bivariate analyzes using the Bayesian approach. The effects considered in the model of Cox and Kaplan-Meier estimator were the year, season and herd of birth, morphometric and dairy type traits. For the production traits the contemporary group was an effect independent of time and the effect of age at childbirth and classes of production as time dependent, in the Weibull animal model. The contemporary group was considered a fixed effect; (linear and quadratic), and the additive and residual genetic effects as random in the linear-threshold model included in the analyzes. The results for Cox regression analysis indicated that the increase of one year of birth, one centimeter in the body length and the width of the croup provided a reduction of 4, 2 and 5%, respectively, in the risk of failure of goats in the herd. The Kaplan-Meier estimators showed significant effects of the classes on the covariables. Goats with higher scores for features related to the mammary system are discarded prematurely from the herd. The class 4 of higher production in volume and constituents of the milk was the one that presented significant difference, reducing the risk of discarding and being associated with the stayability (STAY28) of the goats, using the animal model of Weibull. The heritabilities for STAY28 in both the Weibull model (0.05-0.09) and the linear-threshold model h² (0.07) were low. Estimates of genetic correlation between STAY28 and production traits were zero in the linear-threshold model, but regression of genetic values showed a significant relationship between these traits and STAY28. The STAY28 trait is a viable option for selection of animals with higher genetic values to increase the productive life in dairy goats reflecting in animals with higher yields. Therefore, the improvement of the productive and morphometric traits of the goats have positive effects on the stayability of the animals in the herd